2008
DOI: 10.1080/10489220802142441
|View full text |Cite
|
Sign up to set email alerts
|

Early Acquisition of Basic Word Order in Japanese

Abstract: The acquisition of word order has been one of the central issues in the study of child language. One striking finding from the detailed investigation of various child languages is that from the earliest observable stages, children are highly sensitive to the basic word order of their target language. However, the evidence so far comes mainly from the acquisition of rigid word-order languages. In light of this background, this study presents new evidence that such early sensitivity to basic word order can be ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The SOV structure, more than other structures, provide evidence for this claim that children are sensitive to the standard structure of their own languages, which is consistent with the previous report by Sugiasaki and Koji [12]. Bates demonstrated that Italian-speaking children produced SOV more frequently than any other structures [9].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The SOV structure, more than other structures, provide evidence for this claim that children are sensitive to the standard structure of their own languages, which is consistent with the previous report by Sugiasaki and Koji [12]. Bates demonstrated that Italian-speaking children produced SOV more frequently than any other structures [9].…”
Section: Discussionsupporting
confidence: 80%
“…Sugisaki & Koji, investigated the early acquisition of basic word order in Japanese and suggested that Japanese children were sensitive to the basic word order even though Japanese is a free word order language [12].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of other patterns depend on their difference with respect to the canonical patters. For example, in a recent study in Japanese, a free word order language, Sugisaki (2008) observed emergence of the basic word order first in young Japanese child's utterances. However, currently there is no such data in Hindi to support this conclusion.…”
Section: Implications For Acquisitionmentioning
confidence: 94%
“…as soon as the child starts producing the Verb and its complement (about 18 months old according to Wexler, 1998), and that the word order does not fluctuate (for the OV order, De Haan, 1987 for Dutch; Poeppel and Wexler, 1993 for German;Sugisaki, 2005 for Japanese; for the VO order, Bloom, 1970;Brown, 1973;Lebeaux, 1989, for English). Thus, it can be concluded that the child requires an extremely short period of time (less than several months) for setting head-direction and acquiring scrambling, and that s/he does so at an extremely young age (before or at around the age of two).…”
Section: Research Question and Hypothesesmentioning
confidence: 98%
“…Nevertheless, these word orders are not possible inside the embedded clause, and moreover, the dislocated phrases, S and O respectively, cannot be wh-phrases(Sugisaki, 2005).9 For declarative sentences, the main stress was placed on the phrase immediately preceding the verb, following the ''nuclear stress rule''. For wh-questions, we followed the ''additional stress assignment and deaccenting'' rules, where the wh-word received an additional stress and the rest of the words were deaccented.…”
mentioning
confidence: 99%